Inefficiency and Regulation in Credence Goods Markets with Altruistic Experts - Razi Farukh; Anna Kerkhof; Jonas Loebbing (ZBW - Leibniz Information Centre for Economics, 2020)
We study a credence goods problem - that is, a moral hazard problem with non-contractible outcome - where altruistic experts (the agents) care both about their income and the utility of consumers (the principals). Experts' preferences over income and their consumers' utility are convex, such that experts care less for consumers when their financial situation is bad. In a market setting with multiple consumers per expert, a cross-consumer externality arises: one consumer's payment raises the expert's income, which makes the non-selfish part of preferences more important and thereby induces the expert to provide higher quality services to all consumers. The externality renders the market outcome inefficient. Price regulation partially overcomes this inefficiency and Pareto-improves upon the market outcome. If market entry of experts is endogenous, price regulation should be accompanied by licensing arrangements that cap the number of experts in the market. Our theory provides a novel rationale for the wide-spread use of price regulation and licensing in real-world markets for expert services.
Keywords: D64; D82; D86; L15; L51; 330; altruism; asymmetric information; common agency; credence goods; expert services; externality; inefficiency; moral hazard; regulation